Using the braden scale and photographs to assess pressure ulcer risk - Araújo, Thiago Moura de (2012)
The objective of this paper was to identify critically ill patients at risk for pressure ulcer (PU) using the Braden scale and digital photographs. A sample of 42 subjects was evaluated for 15 days, between March and June 2009, in Fortaleza, Brazil. A total of 47 lesions were identified, 23 (48.9%) as stage I and 24 (51.1%) as stage II. It is necessary for nurses to become familiar with and adopt the technologies used to assess and treat PU in order to lessen the negative effects of this public health problem.